Penentuan Interval Perawatan Komponen Kritis CNC Flame Plasma Cutting Machinemenggunakan MetodeReliability Centered Maintenance (RCM) - Rekadian Arif; Anda Iviana Juniani; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
– The company in Lamongan, East Java is a company focusing on repair and ship building. Based on observations and interviews, it was found that CNC Flame Plasma Cutting is has a high breakdown rate over a period of time. Therefore, this research to identify critical components, determine the appropriate types of treatment and determine the interval of maintenance critical components. In this research, qualitative analysis involves RCM II Decision Worksheet, FBD, FMEA and RPN.Quantitative analysis to determine maintenance interval. The results showed that 19 failure mode and 7 critical components UPS, operating panel, THC (torch height control) plasma, Cutting Nozzle Flame, Nozzle Torch Plasma 1, X axis motor servo, and Y Axis motor servo. For this type of maintenance on Restoration is treated on cutting nozle flame and Y axis motor servo. Discard task on, UPS, THC Plasma, nozzle torch plasma, X axis servo motor. The maintenance Interval 1199,67 hours for UPS components, 1269,85 hours for operating panel, 1646,13 hours for Cutting Nozzle Flame, 1277,51 hours for THC Plasma, 1725,98 hours for Nozzle Torch Plasma, 1125,28 hours for X axis servo motor, and 1106,91 hours for Y Axis servo motor.